Study on the modification effect and mechanism of composite solid waste and steel fiber on the mechanical properties of concrete - Zhao, Qingming; Chen, Li; Wang, Xiaoyu; Zhang, Shengru; Li, Fan (Frontiers in Materials, 2024)
To promote the use of solid waste in concrete production and solve the secondary pollution caused by a large amount of solid waste. The four-factor and four-level orthogonal test method was used to investigate the different replacement rates of coal gangue ceramics (15%, 20%, 25%, 30%), coal gangue ceramic sand (10%, 15%, 20%, 25%), fly ash replacement rates (10%, 15%, 20%, 25%), and steel fiber content (0.30%, 0.60%, 0.90%, 1.2). By using range analysis, variance analysis, matrix analysis, regression analysis, and other analysis methods, the prediction models of primary and secondary factors, optimal dosage, and strength under different factor levels were obtained. The microstructure and strengthening mechanisms of different materials were analyzed by SEM. The results show that the optimal combination of CG substitution rate is 30%, CGS substitution rate is 15%, SF content is 1.2%, and FA substitution rate is 10% for cube compressive strength. For the splitting tensile strength, the optimal combination is a CG substitution rate of 30%, CGS substitution rate of 25%, SF content of 1.2%, and FA substitution rate of 10%. The resulting strength prediction model has high accuracy, which can predict the strength within the range selected by the orthogonal test in this paper, and provide a reference for the application of steel fiber and solid waste in concrete. Contribute to the energy conservation and emission reduction of the construction industry.